EK60 raw multi-frequency (18, 38, 120, 200 kHz) acoustic data collected during RV SONNE cruise SO283 in 2021 to the Benguela Upwelling System work area - Dudeck, Tim; Heinatz, Knut; Lahajnar, Niko (PANGAEA, 2022)
Hydroacoustic raw data from the SO283 cruise aboard the RV Sonne in 2021 (19/03/2021 to 25/05/2021) from the Canary Islands to the Benguela Upwelling System. The hydroacoustics were used as underway measurements during the mooring rescue cruise in the South Atlantic. No biological reference sampling was done on this cruise. We used the Sonne's SIMRAD EK60 system with 4 frequencies: 18, 38, 120 and 200 kHz. The data was limited to 1500m depth. A trigger box was used to avoid interferences with the multibeam echosounders and ADCP during the cruise. Pinging interval is thus less consistent. Ping duration was set to 1.024ms.
Keywords: Benguela Upwelling System; EK60; hydroacoustics; South Atlantic; vertical migration